Changes During the 110 Years of the World Artistic Gymnastics Championships - Grossfeld, A. (Science of Gymnastics Journal, 2014)
This article presents changes, along with historical perspectives, in the World Gymnastics Championships during the last 110 years - 1903 to 2013. Changes include: the events contested, team and individual achievements and dominance, debut of skills, difficulty expansion, judges, scoring, competition format, Finals qualification system, expansion of FIG affiliation, frequency cycle of the WC, number of teams and gymnasts per competition, age requirement of gymnasts, team size, venues, apparatus, devices for learning, education and certification courses, disseminating information, and expanded media coverage.
Keywords: Gymnasts; History; Judges; Rules; dept.ath; ⛔ No DOI found